The role of stem cell transplant (auto and allo) in PTCL and CTCL - Dreger, Peter; Schmitz, Norbert (Hematology, 2024)
In contrast to B-cell lymphoma, the advent of modern targeting drugs and immunotherapeutics has not led to major breakthroughs in the treatment of peripheral T-cell lymphoma (PTCL) to date. Therefore, both autologous and allogeneic hematopoietic cell transplantation (HCT) continue to play a central role in the management of PTCL. Focusing on the most common entities (PTCL not otherwise specified, angioimmunoblastic T-cell lymphoma, and ALK-negative anaplastic large cell lymphoma), we summarize evidence, indications, and points to consider for transplant strategies in PTCL by treatment line. Although cutaneous T-cell lymphomas (CTCLs) are biologically and clinically distinct from the aforementioned PTCL, both disease groups appear to be susceptible to the graft-versus-lymphoma effects conferred by allogeneic HCT (alloHCT), setting the stage for alloHCT as a potentially curative treatment in otherwise incurable CTCL, such as mycosis fungoides/Sezary syndrome. Nevertheless, specific aspects regarding indication and prerequisites for alloHCT in CTCL need to be considered. Given the inherent toxicity of alloHCT and the significant risk of relapse after transplant, only intelligent strategies embedding alloHCT in current PTCL/CTCL treatment algorithms in terms of patient selection, timing, pretransplant preparation, and posttransplant maintenance provide optimal results. New targeted and cellular therapies, either complementary or competitive to HCT, are eagerly awaited in order to improve PTCL/CTCL outcomes.